Climate-driven divergence in biophysical and economic impacts of agrivoltaics - Mengqi Jia; Bin Peng; Kaiyu Guan; David M. Lawrence; Evan H. DeLucia; Alan K. Knapp; Greg A. Barron-Gafford; Madhu Khanna; Danica L. Lombardozzi; Matthew A. Sturchio; Steven A. Kannenberg; Lei Zhao; et al. (Proceedings of the National Academy of Sciences, 2026)
Increasing global demands for food and energy necessitate innovative land-use solutions. Agrivoltaics, colocating solar photovoltaics with agriculture, shows promise, but its widespread adoption faces complex biophysical and economic trade-offs in a changing climate. Here, we develop an integrated biophysical–economic modeling framework to quantify how agrivoltaics affect biophysical and economic impacts across the Midwestern United States under both current and project climate conditions. We find strong regional divergences driven by climate gradients. In the humid eastern Midwest, solar panel shading limits photosynthesis, leading to reduced yields (maize −24%; soybean −16%) and lower farmers’ profitability (maize −16%; soybean −2%) compared to conventional agriculture. Conversely, in the semiarid western region, shading alleviates heat and water stress, moderating yield reductions for maize (−12%) and even boosting soybean yields (+6%), resulting in improved economic returns (−6% for maize; +9% for soybean), for a scenario with 33% photovoltaic ground coverage ratio. Although agrivoltaics generate substantial electrical energy across all regions, high upfront installation costs challenge solar developers compared to standalone solar photovoltaics. However, our analysis identifies “win-win” opportunities where soybean-based agrivoltaics in the semiarid region produce economic benefits for both farmers and solar developers, highlighting the necessity for region-specific designs tailored to local climate conditions. Critically, future climate projections indicate eastward expansion of semiarid conditions, broadening areas where agrivoltaics can mitigate crop yield penalties (even boosting yield) and improve overall profitability, especially under high-emission scenarios. The results provide a mechanistic and economically integrated understanding essential for developing evidence-based and region-specific strategies to scale agrivoltaics in a changing climate.